Enhanced L-β-Aminoisobutyric Acid Is Involved in the Pathophysiology of Effectiveness for Treatment-Resistant Schizophrenia and Adverse Reactions of Clozapine - Kouji Fukuyama; Eishi Motomura; Motohiro Okada (Biomolecules, 2023)
Clozapine is an effective antipsychotic for the treatment of antipsychotic-resistant schizophrenia; however, specific types of A/B adverse effects and clozapine-discontinuation syndromes are also well known. To date, both the critical mechanisms of clinical actions (effective for antipsychotic-resistant schizophrenia) and the adverse effects of clozapine remain to be elucidated. Recently, we demonstrated that clozapine increased the synthesis of L-β-aminoisobutyric acid (L-BAIBA) in the hypothalamus. L-BAIBA is an activator of the adenosine monophosphate-activated protein kinase (AMPK), glycine receptor, GABAA receptor, and GABAB receptor (GABAB-R). These targets of L-BAIBA overlap as potential targets other than the monoamine receptors of clozapine. However, the direct binding of clozapine to these aminoacidic transmitter/modulator receptors remains to be clarified. Therefore, to explore the contribution of increased L-BAIBA on the clinical action of clozapine, this study determined the effects of clozapine and L-BAIBA on tripartite synaptic transmission, including GABAB-R and the group-III metabotropic glutamate receptor (III-mGluR) using cultured astrocytes, as well as on the thalamocortical hyper-glutamatergic transmission induced by impaired glutamate/NMDA receptors using microdialysis. Clozapine increased astroglial L-BAIBA synthesis in time/concentration-dependent manners. Increased L-BAIBA synthesis was observed until 3 days after clozapine discontinuation. Clozapine did not directly bind III-mGluR or GABAB-R, whereas L-BAIBA activated these receptors in the astrocytes. Local administration of MK801 into the reticular thalamic nucleus (RTN) increased L-glutamate release in the medial frontal cortex (mPFC) (MK801-evoked L-glutamate release). Local administration of L-BAIBA into the mPFC suppressed MK801-evoked L-glutamate release. These actions of L-BAIBA were inhibited by antagonists of III-mGluR and GABAB-R, similar to clozapine. These in vitro and in vivo analyses suggest that increased frontal L-BAIBA signaling likely plays an important role in the pharmacological actions of clozapine, such as improving the effectiveness of treating treatment-resistant schizophrenia and several clozapine discontinuation syndromes via the activation of III-mGluR and GABAB-R in the mPFC.